Evaluación de la influencia de la agitación para la producción de biomasa microalgal en un FBR panel plano a escala laboratorio (2017)
The present project evaluates the influence of the agitation on the biomass production in a flat panel photobioreactor, by means of the modification of the sprinklers in the diffuser which form the bubble. As a first step, 3 diffusers with different sprinkler diameters (1, 2 and 4 mm) were made, these were tested to affect the formation of the bubble in the FBR, then by a one-factor analysis of variance ( ANOVA) and t test were used to determine the levels (sprinkler diameters) that affect the response variable (growth rate), selecting two of the 3 diffusers implemented (1 and 2 mm).